THE TRADITION OF EARLY AZAN BEYOND THE FASTING OF RAMADAN IN INDONESIA - usman usman (Indonesian Journal of Islamic Literature and Muslim Society, 2018)
The Azan is an important thing for Muslims as an Islamic ritual that marks the time of Salah, Islamic prayer. Besides being a marker of the time of Salah, it is as well as a marker time of fajr or dawn in the fasting of Ramadan. The Azan is known as an Early Azan which is done before the Azan time of Dawn Prayer. The Early Azan became a reminder to the Muslims who want to do night prayer and pre-dawn meal (meal between midnight and dawn during the fasting of Ramadan). In some parts of Indonesia, this Early Azan has routinely reverberated beyond the fasting of Ramadan. Among the people of Indonesia, the Early Azan beyond the Ramadan functions to wake up people who have not done early evening prayer and for night prayer at the end of the night. Of course, not all Islamic societies are familiar with Early Azan in the fasting of Ramadan. The question is, has it existed since the era of the Prophet Muhammad? so that it sourced from Hadith of the Prophet or the result of Ijtihad which then becomes a tradition for Muslims in Indonesia.